The history of Jemmy and Jenny Jessamy - Haywood, Eliza Fowler, 1693?-1756 (Eighteenth-century novels by women., 2005)
The author of over eighty novels, plays, and volumes of poetry, Eliza Haywood is one of the most prolific and high-profile female authors of the eighteenth century. Her last novel, The History of Jemmy and Jenny Jessamy, is original for its unsentimental realism in its depiction of marriage and courtship among the leisure classes of the mid-eighteenth century. In his new introduction, editor John Richetti examines how Haywood's amusing and engaging prose explores the subtleties of eighteenth-century courtship. Out of print since the early nineteenth century, The History of Jemmy and Jenny Je.